Giant little ones - Behrman, Keith, 1963-; Wiggins, Josh; Mann, Darren; MacLachlan, Kyle, 1959-; Bello, Maria, 1967-; Hickson, Taylor, 1997-; Godfree, Guy; Pereira, Sandy; Brook, Michael; Wolfe (Wolfe, 2019)
Franky Winter and Ballas Kohl have been best friends since childhood. They are high school royalty: handsome, stars of the swim team and popular with girls. They live a perfect teenage life, until the night of Franky's epic seventeenth birthday party, when Franky and Ballas are involved in an unexpected incident that changes their lives forever. It is a heartfelt and intimate coming -of -age story about friendship, self-discovery and the power of love without labels.
Title from disc surface.
Originally released as a motion picture in 2018.
Widescreen.
Director of photography, Guy Godfree ; editor, Sandy Pereira ; music, Michael Brook.
Josh Wiggins, Darren Mann, Kyle MacLachlan, Maria Bello, Taylor Hickson.
MPAA rating: R; for sexual content, language and some drug/alcohol use - all involving teens.
Keywords: Best friends -- Drama; Friendship -- Drama; Young gay men -- Drama; High school students -- Drama; Feature films; Fiction films; Coming-of-age films